Proximate Characteristics of Low Glycemic Index Instant Rice with Variations in Storage Temperature and Drying Time - Rusdin, Ilmiani; Laga, Amran; Pirman, Pirman; Sulaiman, Muh. Restu Ray Amir; Irwan, Irwan (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2023)
Paddy (Oryza sativa L.) is the staple food for the Indonesian people, commonly processed into rice. Consumption of rice through the cooking process takes 30 to 40 minutes. With the relatively long preparation process, the idea of instant rice processing is the answer for a shorter rice preparation process. Instant rice processing can be done using the autoclaving-retrogradation method. This study aimed to determine the proximate profile of low glycemic index instant rice, including water, ash, protein, fat and carbohydrate content. The research method was carried out by varying the storage temperature (without cooling, cooling at 4 °C and freezing at -4 °C) and drying time (0, 2, 4, 6, 8 and 10 hours). The proximate average yield of instant rice water content ranged from 60.43% to 10.61%; ash content 0.49% to 0.35%; protein content 9.61% to 7.70%; fat content 0.76% to 0.42% and carbohydrate content 77.27% to 75.19%. Thus, the short rehydration time indicates that the resulting product is included in instant food products because it takes less than 5 minutes to be consumed. In addition, reducing the glycemic index of rice can be done by retrograding starch to obtain resistant starch through a continued pressure cooking process by the cooling process. Reducing starch digestibility and glycemic index in rice through resistant starch formation can reduce the adverse effects of rice consumption as a staple food.